Parental Responsibility in Elementary School Children's Education: Integration of the Tarbiyatul Aulad Concept and Islamic Family Law - Yudhi Hadiamsyah; Atiek Nazli Rahmatika (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2026)
This study examines the gap between the normative demands of parental responsibility in children's education according to the concepts of Tarbiyatul Aulad and Islamic Family Law and the reality of its implementation in Islamic elementary schools (SD/MI), as well as exploring responses to the GEMAR program. The novelty of this research lies in three aspects: (1) the integration of Abdullah Nashih Ulwan's seven educational dimensions with Article 80 of the Compilation of Islamic Law (KHI), which has previously been interpreted only in economic terms; (2) the first evaluation of the GEMAR program in Islamic elementary schools (madrasah ibtidaiyah); (3) the development of a normative-empirical integration model that has not existed in previous studies. This research employed a qualitative approach with a single case study design. Data were collected through in-depth interviews (18 parents, 6 teachers, 1 principal, 8 students), participatory observation, and documentation. The findings indicate: (1) the ideal concept encompasses seven aspects and five educational methods, as well as the mandate of Article 80 KHI; (2) implementation remains partial, with psychological and sexual education being neglected and minimal paternal involvement (the fatherless phenomenon at only 26.7%); (3) the GEMAR program shows positive contributions but still faces challenges in the form of symbolic participation. The contributions of this research include expanding the interpretation of Article 80 KHI, critiquing gender constructs in Islamic family law, and providing evidence-based policy recommendations for the GEMAR program. In conclusion, synergy among family, school, and government is essential, emphasizing the revitalization of the father's role and the dissemination of Ulwan's seven aspects. Policy implications are context-specific and require further multi-site testing.